SISTEM INFORMASI PENGOLAHAN DATA PENDUDUK BERBASIS WEB UNTUK DESA PERSIAPAN PAJANGAN - Aang Suvandi; , Muhammad Fauzi Zulkarnaen; Saeful Hamdi (Lembaga Pengembangan Kinerja Dosen, 2022)
Abstract The Pajangan Village Office is one of the villages in Kopang District. Currently, the use of computers is used by the village government to store data such as population data, village profile data and so on are still in the form of files created using Microsoft Word and Excel, there is even some data recorded in a book before being recapitulated to make reports. The system that is running now has many shortcomings, including errors in writing or inputting data, takes a long time in the search process, and the occurrence of damage to the computer that causes the data to be lost, In this case the author aims to produce a Web-based population data processing information system for the Pajangan Preparation Village in storing data and processing population data so that the data stored is safe and easy to process, searching, and presenting data by the village government to the community. Keywords: Information System, Data Processing, Population, Web